Kynurenic Acid Inhibits the Electrical Stimulation Induced Elevated Pituitary Adenylate Cyclase-Activating Polypeptide Expression in the TNC - Körtési, Tamás; Tuka, Bernadett; Tajti, János; Bagoly, Teréz; Fülöp, Ferenc; Helyes, Zsuzsanna; Vécsei, László (Frontiers in Neurology, 2018)
Background: Migraine is a primary headache of imprecisely known mechanism, but activation of the trigeminovascular system (TS) appears to be essential during the attack. Intensive research has recently focused on pituitary adenylate cyclase-activating polypeptide (PACAP) and the kynurenine systems as potential pathogenic factors. Aim: We investigated the link between these important mediators and the effects of kynurenic acid (KYNA) and its synthetic analogue (KYNA-a) on PACAP expression in the rat trigeminal nucleus caudalis (TNC) in a TS stimulation model related to migraine mechanisms. Methods: Adult male Sprague-Dawley rats were pretreated with KYNA, KYNA-a, the NMDA receptor antagonist MK-801 or saline (vehicle). Next, the trigeminal ganglion (TRG) was electrically stimulated, the animals were transcardially perfused following 180 min and the TNC was removed. In the TNC samples, PACAP1-38-like radioimmunoactivity was measured by radioimmunoassay, the relative optical density of preproPACAP was assessed by Western blot analysis, and PACAP1-38 mRNA was detected by real-time PCR. Results and conclusion: Electrical TRG stimulation resulted in significant increases of PACAP1-38-LI, preproPACAP, and PACAP1-38 mRNA in the TNC. These increases were prevented by the pretreatments with KYNA, KYNA-a, and MK-801. This is the first study to provide evidence for a direct link between PACAP and the kynurenine system during TS activation.